The quest for global dominance / Vijay Govindarajan; Anil K Gupta - Govindarajan, Vijay
A resource for managers who need an informative and practical guide to the subject of global business strategy. The book provides the intellectual trail of where we've been, where we are, and where we are headed in a global business environment